Evidence for alignment of the rotation and velocity vectors in pulsars – II. Further data and emission heights - johnston, S.; Kramer, M.; Karastergiou, A.; Hobbs, G.; Ord, Stephen; Wallman, J. (Wiley-Blackwell Publishing Ltd., 2007)
We have conducted observations of 22 pulsars at frequencies of 0.7, 1.4 and 3.1 GHz and present their polarization profiles. The observations were carried out for two main purposes. First, we compare the orientation of the spin and velocity vectors to verify the proposed alignment of these vectors by Johnston et al. We find, for the 14 pulsars for which we were able to determine both vectors, that seven are plausibly aligned, a fraction which is lower than, but consistent with, earlier measurements. Secondly, we use profiles obtained simultaneously at widely spaced frequencies to compute the radio emission heights. We find, similar to other workers in the field, that radiation from the centre of the profile originates from lower in the magnetosphere than the radiation from the outer parts of the profile.